Report on Development of Tribal Areas National Committee on the Development of Backward Areas - Planning Commission (Planning Commission, 1981)
The National Committee on the Development of Backward Areas emphasized a comprehensive and family-focused approach to tribal development in India, highlighting the persistent socio-economic challenges faced by Scheduled Tribes. The Tribal Sub-Plan strategy seeks to provide both developmental programmes and basic needs while considering the presence of other weaker sections, such as Scheduled Castes, who have symbiotic relationships with tribal communities. Despite the creation of institutional infrastructure, low literacy levels, land alienation, and limited utilization of resources by tribal communities persist, underscoring the need for more effective and sensitive administration. Tribal areas are diverse, ranging from high-concentration populations in the North-East to smaller pockets in southern states, with livelihoods primarily dependent on agriculture and allied activities, often with small landholdings. The committee recommends an Integrated Tribal Development Project (ITDP) approach to address area-specific issues, including primitive communities, forest-based economies, shifting cultivation, industrial influences, and urbanizing regions. Development strategies must prioritize education and health services to strengthen community resilience during socio-economic transitions, and interventions should follow a beneficiary-oriented, project-based framework to enhance productive and earning capacities. Institutional reforms, including clear administrative and financial structures, are essential for effective implementation, with ITDPs streamlined and restructured accordingly. Additionally, the delineation of Tribal Sub-Plan areas should include regions where Scheduled Tribes and Scheduled Castes together constitute at least 50 percent of the population, ensuring inclusive development and equitable access to resources.
Planning Commission, Government of India
Planning Commission, Government of India
Keywords: Tribal Development, Scheduled Tribes, Tribal Sub-Plan, Integrated Tribal Development Project, Backward Areas, Education, Health Services, Land Alienation, Livelihood, Regional Planning, Socio-Economic Integration, Administrative Structures